Local Wisdom "Awetako Ena Agapida" on Employee Performance at Nabire Airport and Meepago Region Airport Papua - Juprianto Pali; Zainur Hidayah; Vincentius Rachmadi Parmono (Studi Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: This study aims to determine the impact of the implementation of local wisdom Aweta Ko Enaa Agapida on the performance of Civil servant at Nabire Airport Office and Meepago Papua area. Research methodology: This study uses a qualitative approach with a descriptive method in describing and revealing the impact of local wisdom on Civil servant performance in Nabire Airport Office and Meepago Papua area. Data and information were analysed with the stages of data collection, data reduction, data presentation and conclusion. Results: The results of the study indicate that the implementation of Aweta Ko Ena Agapida local wisdom in the Nabire Airport Office and Meepago Papua area has a positive influence on the performance of the State Civil Apparatus in several ways. First, Civil servants become more motivated and good at managing time in their daily lives. Second, they better understand their main tasks and functions, with high enthusiasm and willingness to learn. Lastly, Civil servant's performance in the company also improved, especially in terms of time discipline and service to airport users. Limitations: This study is limited to the subject of employees at Nabire Airport and Meepago Papua Regional Airport. Contribution: This research can be used by government organisations and companies in Papua as additional information in applying noble values in local wisdom to improve employee performance in Papua. Keywords: Evaluation, Inhibiting Factors, Local Wisdom and Strategies, Supporting Factors